Supply chain collaboration : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Technology in Decision Science at Massey University - Simatupang, Togar Mangihut (Massey University, 2004)
There is general acceptance within the literature that supply chain collaboration will become a focus area for research in supply chain management. Although collaboration has been examined widely in a variety of different contexts, relatively little attention has been given to systematically drawing them together. This study is thus conducted to offer an integrative framework in the context of an interorganisational supply chain to define collaboration by identifying its different elements and provides empirical evidence to support the theoretical framework. This framework would further allow the participating members to understand and examine the strategic importance of these elements of collaboration and what needs to be done to gain the benefits of collaboration. The study includes a literature review, the discontent model, a theoretical framework for supply chain collaboration, measuring the level of supply chain collaboration, supporting the theory with empirical evidence, an innovative scheme for benchmarking, and an empirical study of benchmarking supply chain collaboration. The theoretical framework offered in the study incorporates the five elements of collaboration, namely, a collaborative performance system, information sharing, decision synchronisation, incentive alignment, and streamlined intercompany business processes. To provide empirical evidence, supply chain collaboration between retailers and suppliers was chosen as a unit of analysis and data were collected from a survey of New Zealand companies. Based on the survey results, the three empirical studies reported in this thesis provide the basis for testing a new measure for the extent of supply chain collaboration, testing the hypotheses on the relationship between supply chain collaboration and operational performance, and presenting the benchmarks for classifying high and low performing supply chains. Empirical evidence shows that collaboration between retailers and suppliers has a significant influence on operational performance.
Keywords: Business logistics; Management; Decision science; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management